Composition and thermal profile of crude palm oil and its products - Che Man, Y. B.; T., Haryati; Ghazali, H. M.; Asbi, B. A. (Wiley, 1999)
Gas‐liquid chromatography and high‐performance liquid chromatography (HPLC) were used to determine fatty acids and triglyceride (TG) compositions of crude palm oil (CPO), refined, bleached, and deodorized (RBD) palm oil, RBD palm olein, and RBD palm stearin, while their thermal profiles were analyzed by differential scanning calorimeter (DSC). The HPLC chromatograms showed that the TG composition of CPO and RBD palm oil were quite similar. The results showed that CPO, RBD palm oil, RBD olein, and superolein consist mainly of monosaturated and disaturated TG while RBD palm stearin consists mainly of disaturated and trisaturated TG. In DSC cooling thermograms the peaks of triunsaturated, monosaturated and disaturated TG were found at the range of −48.62 to −60.36, −25.89 to −29.19, and −11.22 to −1.69°C, respectively, while trisaturated TG were found between 13.72 and 27.64°C. The heating thermograms of CPO indicated the presence of polymorphs β 2 ′, α, β 2 ′, and β 1 . The peak of CPO was found at 4.78°C. However, after refining, the peak shifted to 6.25°C and became smaller but more apparent as indicated by RBD palm oil thermograms. The heating and cooling thermograms of the RBD palm stearin were characterized by a sharp, high‐melting point (high‐T) peak temperature and a short and wide low‐melting point (low‐T) peak temperature, indicating the presence of occluded olein. However, for RBD palm olein, there was only an exothermic low‐T peak temperature. The DSC thermograms expressed the thermal behavior of various palm oil and its products quite well, and the profiles can be used as guidelines for fractionation of CPO or RBD palm oil.